PENGARUH KONSENTRASI DAN LAMA INKUBASI TERHADAP AKTIVITASENZIM SELULASE DARIKAPANG Aspergillusniger - Pujiati, Pujiati; Kiswardianta, R. Bekti; Solikati, Wiwin (IKIP PGRI MADIUN, 2014)
Aspergillusniger is one type of mold that has a high ability to produce cellulases. Cellulases in the manufacturing process required the right conditions in order to obtain optimum quality and quantity. This study aims to determine the effect of different concentrations of inoculum and incubation time on cellulases activity of Aspergillusniger.The method used was a quantitative experiment with pattern completely randomized design(CRD) two factorial. Treatment research includes different of inoculum (K) which are 10%(K1), 15% (K2), 20% (K3) and incubation times (T) are 5 days (T1), 7 days (T2), 9days (T3). The datawere taken from the treatment is glucose levels of cellulases activity using theNelson Somogyi method. Analysis data using ANOVA two lanes with 5% of a significance level and continued to test Honestly Significant Difference (HSD). The results showed that: Fhit>Ftabso that there are significant differences in inoculum concentrations and incubation time of cellulolytic activity from Aspergillusniger.The highest glucose levels obtained in K3T1 treatment (20% of concentration and 5days of incubation time) with 0.072%.Keywords: Aspergillusniger, glucose, cellulases activity